High efficiency low thermal resistance semiconductor laser with novel insulating layer and coating film. Issue 14 (3rd June 2021) - Wang, Yuancheng; Qi, Aiyi; Wang, Yufei; Qu, Hongwei; Zheng, Wanhua
Abstract: Thermal effect of semiconductor lasers is the biggest challenge to the development of semiconductor lasers. This problem limits the life and performance of high‐power laser diode. In this letter, we have reduced the thermal resistance of laser to enhance its heat dissipation capability. For this, we choose aluminium nitride (AlN) to replace traditional materials as insulating layer, as well as a passivation film for facet coating. The impact of insulation layer and facet coating on the thermal rollover process is analyzed. Finite element method simulations are compared with the experimental result. The comparison shows that the thermal resistance of the laser with the new insulating layer is reduced compared with normal laser diodes (LD). Eventually, the maximum conversion efficiency is 67.5% at room temperature and thermal resistance is 1.81C° W–1.